Correlation between productivity components and yield of cultivars in different harvests (Research, Society and Development, 2024)
Current information on the performance of cultivars available on a regional scale is scarce and of fundamental importance for the various segments of the soybean production chain. The objective of this work is to present the productivity of different soybean cultivars in the 2021/22 and 2022/23 harvests in the Celeiro region of the State of Rio Grande do Sul and evaluate which productivity component had the highest correlation with productivity in these harvests. The following evaluations were carried out: Productivity, Number of Vegetables and Number of Grains per plant, Weight of a Thousand Grains and Plant Population. For statistical analysis, the Scott-Knott test was used, using the SASM-AGRI program. For correlation tests between components and productivity, Pearson correlation was used. In the 2021/22 harvest, the cultivars DM 64i63, NS 6601, CZ 16B17 and COMPACTA stood out from the others, while in the 2022/23 harvest, the CROMO and C2600 cultivars were the cultivars with the best productive performance. Regarding productivity components, the highest correlations were for the Number of Vegetables per Plant for the 2021/22 harvest and Weight of Thousand Grains for the 2022/23 harvest.